The associations and its role in devoting for museums’ demand - مالك شليح توفيق; عسلي حليمة (International Journal of Social Communication, 2022)
This paper is based on the role of associations as one of the forms of new social-upbringing institutions in promoting the museum institutional presence within societal value systemby devoting association’s efforts to establish the cultural practices among individuals, promoting the cultural consumption of these spaces, and establishing visitors' relationship with the museum by using associations' power and resources by setting up their programs on a basis to support the cultural consumption of museums. The object of this paper was based on a descriptive study of the museum in its relation with the Society, by presenting the mechanisms and strategies of associations in enshrining the concept of individual personal demand, by giving a conceptual analysis of the museum's historical common points, with the associations as open spaces, with a socio-cultural dimension, by which associations stand as a support for the museum activity and cultural consumption in its various forms.